PS01.181: ESOPHAGECTOMY FOR ESOPHAGEAL CARCINOMA TO ELDERLY PATIENTS OVER 75 YEARS OLD. (14th September 2018) - Ujiie, Naoto; Taniyama, Yusuke; Sakurai, Tadashi; Heishi, Takahiro; Sato, Chiaki; Okamoto, Hiroshi; Maruyama, Shota; Onodera, Yu; Kamei, Takashi
Abstract: Background: Recently, operation cases of elderly patients are increasing in esophageal carcinoma. Because elderly patients often have pre-existing disease and may easily cause postoperative complications, it is necessary to consider whether surgical treatment is appropriate for those elderly patients. The aim of this study is to investigate the safety of esophagectomy for elderly patients with esophageal carcinoma. Methods: All 483 patients who underwent esophagectomy for esophageal carcinoma between April 2007 and March 2015 were included in this study. Patients were divided into two groups: elderly group (over 75 years old: n = 72) and control group (under 75 years old: n = 411). The short and long-term outcomes were retrospectively examined to those groups. Results: In the elderly group, their median age was 77 [75–85] and all of their performance status was 0 or 1, except 4 patients. 66 cases of the elderly group had some comorbidity, which was significantly higher than that of the control group (93.0 vs. 80.2%, P = 0.007). Pre-surgical treatment was performed to 38.9% of the elderly group, whereas 58.9% in the control group ( P = 0.002). No significant differences were demonstrated in clinical stage, occupation site, histological type and pathological stage between these groups. The operation time was relatively shorter in the elderly group compare to the control group (549 vs. 585min, P = 0.018). The number of dissected lymph node was also smaller in elderly group (31 vs. 35, P = 0.048). The postoperative complications such as pneumonia, recurrent laryngeal nerve paralysis did not show any difference between these groups. The 5-year overall survival rate (OS) and the 5-year disease specific survival rate (DSS) also did not show statistical differences between the elderly and control group (OS: 53.0 vs. 57.0%, P = 0.765; DSS: 64.6 vs. 62.7%, P = 0.605). Conclusion: Between elderly and control group, there was no difference in postoperative complication and long-term survival. This study confirmed the safety of esophagectomy for elderly patients with esophageal carcinoma by reducing treatment stress such as neoadjuvant therapy, extended operation time and extensive lymphadenectomy. Disclosure: All authors have declared no conflicts of interest.